ANALISIS SEGMENTASI PASAR USAHA FURNITURE CV IRIAN’S INDAH DI TIMIKA - Murlin Andaka; Muh. Sabir (CV. Adiba Aisha Amira, 2025)
The purpose of this study is to determine how the market segmentation of CV Irian's Indah furniture business is carried out. The types of data used in this study are quantitative and qualitative data. The data collection techniques used are interviews, observation, and questionnaires. The analysis tool used in this study is factor analysis. Based on the analysis and discussion, it can be concluded that the crosstab analysis shows that the most dominant gender with geographical segmentation is female with geographical segmentation indicating rural areas. The demographic crosstab analysis with psychographic segmentation shows that female respondents are more dominant in choosing local city brands as psychographic segmentation. The demographic cross- tab analysis with behavioural segmentation shows that women dominate in choosing quality as behavioural segmentation. The demographic cross-tab analysis with future preference segmentation shows that women dominate in choosing neutral as future preference.